2022
DOI: 10.1186/s12891-022-05139-6
|View full text |Cite
|
Sign up to set email alerts
|

Fear of movement and emotional distress as prognostic factors for disability in patients with shoulder pain: a prospective cohort study

Abstract: Background Shoulder pain is a prevalent and often long-lasting musculoskeletal disorder. The overall prognosis of shoulder pain is highly variable with 40–50% of patients reporting persistent pain 6–12 months after consulting a clinician. The evidence for psychological prognostic factors for patients with shoulder pain is inconsistent. Therefore, the objective of this study was to investigate the association between fear of movement and emotional distress at presentation and self-reported disab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 44 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…Pain and depression share common neurological pathways, leading to helplessness and fear of physical activity [ 85 ]. The detrimental impact of adverse mental health outcomes and pain-induced disability has been described in other chronic pain conditions [ 25 ], such as chronic neck pain [ 98 ] and chronic shoulder pain [ 99 , 100 ]. Psychological distress has been identified as a mediator of the relationship between pain and pain-induced disability in persons with back pain [ 101 , 102 ], which is also a symptom of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pain and depression share common neurological pathways, leading to helplessness and fear of physical activity [ 85 ]. The detrimental impact of adverse mental health outcomes and pain-induced disability has been described in other chronic pain conditions [ 25 ], such as chronic neck pain [ 98 ] and chronic shoulder pain [ 99 , 100 ]. Psychological distress has been identified as a mediator of the relationship between pain and pain-induced disability in persons with back pain [ 101 , 102 ], which is also a symptom of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial factors can partially explain the clinical outcomes of resisted exercise programs. 31,200,203,207 A 2019 systematic review 200 identified that baseline measures of treatment expectations and self-efficacy were predictive of patient-reported outcomes with rehabilitation for shoulder pain. Prospective studies 31,207 identified expectations of recovery, self-efficacy, kinesiophobia, and pain catastrophizing at baseline to be predictive of patient-reported outcomes with rehabilitation for musculoskeletal shoulder pain.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…30,31,[200][201][202][203][204][205][206] Most recently, higher levels of emotional distress and kinesiophobia were associated with greater disability over one year in patients with shoulder pain. 207 These psychological factors may develop concurrently with pain, or precede the development of symptoms. A longitudinal study reported the development of shoulder pain concurrently with elevated levels of anxiety.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
See 2 more Smart Citations